Conceptual hydrological response models of selected arid soilscapes in the Douglas area, South Africa - Tinnefeld, Martin (University of the Free State, 2016)
The conceptual hydrological response model (CHRM) is a powerful tool, able to transfer hydrological information of hillslopes. Soil, a first order control of partitioning of water flow, is often the only source of information of hillslope water flowpaths and storage mechanisms. Conceptual hydrological models applied at different scales, serve as the framework to understand and structure the hydrological response of sites, hillslopes and catchments. They complement decision making and planning of natural resource allocation and delineation for land-use change in ecology, agriculture, mining and urbanisation. Soil morphology, chemistry and hydrometrics are used singularly and complimented in combination as indicators and controllers of hydrology to construct CHRMs. The more accurate the input parameters of soil morphology, chemistry and hydrometrics, the more accurate the final CHRM. Arid soils of South Africa have been neglected to be investigated for their hydrological properties. This is due to the low rainfall, infrequent hydrological response and resulting low output of data. Where such hydrological studies have been performed under higher rainfall climatic zones, soil has been found to respond as a store and conduit of water. These are referred to as storage mechanisms and flowpaths within the soil and can be determined by studying the soils’ morphology, improved by soil chemistry and are verified by application of hydrometrics. Soil distribution patterns are not random and are influenced by hillslope hydrology. The vastness of the arid regions of South Africa, make it difficult to select singular representative hillslopes. However, by describing the soil distribution patterns of randomly distributed detailed soil maps within different land types, allowed for soil distribution trends to be identified in this study. These soil distribution trends were seen to coincide with terrain morphological units. Representative modal profiles were selected on dominant and representative terrain morphological units of 4 different land types on criteria that they are representative soils of the land type and sites. The soils have well developed horizons resulting in vertical pedological variation including different degrees of carbonate precipitation. Methodology of other research, to interpret morphology in higher rainfall regions of South Africa, was used to construct a conceptual hydrological response model for the arid hillslopes and the region in general. Hydrological properties of modal profiles, were used to confirm the concepts. A class 1 hillslope hydrological response: soil/bedrock interflow to wetland; dominates on all four sites. Individual sites and their respective soil distribution patterns showed fast pedon recharge to the soil/rock interface. Pedon interflow at higher lying topographical positions with associated steeper slope, contributed to carbonate as dominating morphological flowpath indicator lower lying in the landscape. This is primarily driven by a low rainfall/high evapotranspirative demand of arid climates. Topographically lower lying soils showed reduced infiltration due to high alluvial clay and silt deposits and/or soil matrix saturation with carbonate precipitation sufficient to reduce the permeability of the soil.
Dissertation (M.Sc.Agric. (Soil, Crop and Climate Sciences))--University of the Free State, 2016
Keywords: Arid hydropedology; Conceptual hydrological model; Soil-map-hydrology; Flowpath; Storage mechanism